TRANSFORMASI POLA PELAYARAN DAN PERDAGANGAN VOC DI NUSANTARA PADA ABAD 16-18 M - Gunawan Bulfi; Hamdi Ramadhan; Putri Dahlia (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2026)
Indonesia occupies a strategic position within international shipping and trade networks due to its location along global trade routes and its abundant natural resources, particularly spices. During the 16th century, maritime and commercial activities in the Indonesian archipelago flourished through networks involving local, Asian, and European traders. This context provides a basis for analyzing the transformations that occurred following the establishment of the Vereenigde Oostindische Compagnie (VOC) in 1602. This study aims to examine the role of ships as links in trade, as well as the transformations and commodities traded by the VOC in the archipelago from the 16th to the 18th centuries. It does so by comparing conditions before and after the VOC's arrival, specifically regarding changes in shipping routes, vessel types, and traded commodities. The study employs a library research methodology, incorporating the stages of the historical method: heuristics, source criticism, interpretation, and historiography. The findings indicate that prior to the VOC's arrival, shipping and trade networks in the archipelago operated relatively openly through major ports connected to broader Asian trade networks. Following the VOC's arrival in the 17th century, significant transformations occurred, including the seizure of strategic ports, the realignment of shipping routes to serve VOC monopoly interests, the utilization of a VOC fleet supported by local vessels, and the control of key commodity trades—such as cloves, nutmeg and pepper. These transformations shifted the maritime trade structure of the archipelago from a relatively open system to one that was centralized and controlled by the VOC through monopoly policies that persisted until the 18th century.